Chad Economic and Poverty Update under COVID-19, Spring 2020 - Tchana Tchana, Fulbert; Kassim, Olanrewaju; Savadogo, Aboudrahyme; Ouedraogo, Aissatou; Coulibaly, Mohamed (World Bank, Washington, DC, 2020)
Up to February 2020, Chad’s economy continued its gradual, but mild recovery, supported by a substantial increase in oil and agriculture production. Since March 2020, like in the rest of the world, the Coronavirus (COVID-19) pandemic has dramatically changed Chad’s macroeconomic outlook. Chad’s economic prospects have not only been clouded, but they remain subject to considerable downside risks. To mitigate the negative impact of Coronavirus (COVID-19) on Chad, the authorities announced economic and social measures to support households and private companies in recent months. The authorities are to continue to strengthen some measures already taken while introducing new measures to protect lives, livelihoods, and the future.